Unpacking the Myths: Inequities and maternal mortality in South Asia - IMRANA QADEER (Development, 2005, 48(4) (120-126), 2005)
Imrana Qadeer examines whether the Millennium Development Goals (MDG) are different from past approaches to maternal mortality in South Asia and critically assesses how they address the underlying inequities that determine reproductive health policies. She argues that policies to reduce maternal mortality can work, but that these strategies require a long-term perspective that is based on holistic development of the people and not just a select section given that maternal mortality is largely the outcome of poor general health and socio-economic constraints.